Anatomical Snuff Box Arteriovenous Fistulas for Haemodialysis - Muhammad Waqas Raza ,Khurram Waqas , Moazam Ayub,Muhammad Hanif , Muhammad Mussadiq Khan (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate snuffbox fistulas in patients with end stage chronic renal failure and to describe the complications and patency rates of snuff box fistulas. Methods: This descriptive study enrolled patients with end stage renal chronic renal failure, in whom anatomical snuff box fistulas were created. All the patients had adequate caliber vessels (greater than 2mm diameter cephalic vein and radial artery) in an end to side configuration. Presence of a palpable thrill or bruit on auscultation was considered a successful fistula. Fistulas which never provide vascular access whether due to poor vein maturation, thrombosis or any other reason were designated primary failure. Fistulas that failed after a period of use were designated secondary failures. Complications and failure rates were determined at 1 month, 3 months, 6 months and 12 months. Results:A total of 71 AV fistulas were created over a period of 8 years. Sixteen patients (22.53%) developed fistula failure over a follow up of one year. Thrombosis was the commonest cause of primary failure and Juxta anastamotic stenosis was the commonest cause of secondary failure . Overall patency was 66 % at one year. Both primary and secondary failures were higher in females and diabetics. Conclusion: Anatomical snuff box arteriovenous fistulas have several advantages over the more commonly performed Brescia-Cimino radiocephalic fistulas at the distal forearm. Snuff-box fistulas have satisfactory outcome and patency rate and advantage of preservation of more proximal sites for any future fistula construction in case of failure.